Linear kinematics of the underwater undulatory swimming phase performed after two backstroke starting techniques - de Jesus, K.; de Jesus, K.; Machado, L.; Fernades, R.; Vilas-Boas, J. P. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to analyze the effects on relevant kinematic parameters of the underwater undulatory swimming (UUS) phase of the repetition of these UUS cycles and of the starting technique used: the one with the feet parallel and entirely immerged (BSFI) and the other with the feet parallel and entirely emerged (BSFE). Four high level swimmers performed 3x15 m maximal sprints using each technique (BSFI and BSFE). In both starting techniques the mean horizontal velocity and horizontal amplitude were greater for the 4 initial UUS cycles than the last 4 ones. At BSFI, the 4 initial UUS cycles showed greater mean frequency than the last 4 ones. No differences were observed between BSFI and BSFE for the 4 initial UUS cycles. Coaches should consider the frequency of UUS cycles to optimize underwater phase performance at BSFI and BSFE.